A high-stability PA-PE composite material for food and preparation method thereof

By modifying the combination of PA66 with HDPE and glass fiber, combining compatibility and antioxidants, the problems of high migration and poor stability of PA-PE composite materials under high temperature, high oil, acidic or alkaline conditions are solved, and the problem of high migration and poor stability of PA-PE composite materials is achieved. High stability and excellent mechanical properties in the food field.

CN115850965BActive Publication Date: 2025-01-14GUANGDONG DOSN SCI &TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211633702.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-01-14
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

The existing PA-PE composite materials have high migration volume and poor stability under high temperature, high oil, acidic or alkaline conditions, which is difficult to meet the high stability requirements in the food field.

Method used

Using the combination of modified PA66 with high-density polyethylene (HDPE) and hydrolyzed glass fiber and other components, the compatibility and stability of the material are improved by the addition of compatible and antioxidants, and extruded by parallel twin screws. The preparation method for the mechanism improves the mechanical properties and heat resistance of the material.

Benefits of technology

It achieves high stability of PA-PE composite materials, excellent mechanical properties, low water absorption, good heat resistance, acid and alkali resistance, and oil resistance. It is suitable for the preparation of food contact materials, especially kitchen utensils.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer composite materials, and relates to a high-stability PA-PE composite material for food, a preparation method and application thereof, and the PA-PE composite material comprises the following components in parts by weight: 40-70 parts of polyamide, 15-40 parts of polyethylene, 8-30 parts of glass fiber, 2-8 parts of compatibilizer, 0.5-5 parts of antibacterial agent, 0.1-2 parts of antioxidant, and 0.1-2 parts of auxiliary agent. The PA-PE composite material of the present invention has both excellent mechanical properties and high stability, is suitable for the field of food, and the product prepared therefrom has low migration during contact with food, no peculiar smell during cooking, no deformation when heated, stable size, low shrinkage, water resistance, oil resistance, acid and alkali resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer composite materials, and relates to a PA-PE composite material and a preparation method thereof, and more specifically to a high-stability PA-PE composite material dedicated to food and a preparation method thereof. Background Art

[0002] Plastic is one of the most commonly used materials in the field of food packaging. It is widely used in the preparation of food containers, packaging materials, and various molded products such as equipment and utensils for the food industry. In recent years, as people's attention to food safety has gradually increased, the hygienic safety of plastic products has also received widespread attention from the society. During the contact between food contact materials and food, under high temperature, high oil, acidic or alkaline conditions, monomers, oligomers, additives, auxiliary agents, decomposition products, etc. in the materials may migrate into food and affect people's health. Therefore, people began to pay attention to the development and application of special food materials with good mechanical properties, high stability and low migration.

[0003] Polyamide (PA), commonly known as nylon, is a general term for thermoplastic resins containing repeating amide groups -[NHCO]- on the main chain of the molecule. Its amide groups are polar and can form hydrogen bonds, so it has excellent mechanical properties. It is a relatively tough engineering plastic and has good heat resistance and oil resistance. It is often used to prepare plastic tableware and kitchen utensils, such as nylon spoons and shovels. However, PA materials easily absorb water, have poor stability, and have low impact strength at low temperatures.

[0004] Polyethylene (PE) is a thermoplastic resin obtained by polymerization of ethylene. It has excellent low temperature resistance, good chemical stability, and can withstand the corrosion of most acids and alkalis. Polyethylene has good water resistance and low water absorption, generally less than 0.01%; however, the mechanical properties of polyethylene are average, with low tensile strength, poor creep resistance, and low heat resistance.

[0005] In order to obtain a composite material with good properties of both PA and PE, the two need to be blended, but the blend system of PA and PE is an extremely incompatible blend system. The structures and morphologies of the two polymers are very different, and the degree of mixing is poor. Even if mixed, the mixed material usually shows macroscopic phase separation, and the prepared blend often shows stratification, has a high migration amount under high temperature, high oil, acid and alkali conditions, and has poor stability.

[0006] Therefore, there is an urgent need to provide a new PA-PE composite material to meet the high stability requirements in the food field. Summary of the invention

[0007] The object of the present invention is to provide a PA-PE composite material having both excellent mechanical properties and high stability and a preparation method thereof.

[0008] Based on the above invention object, the technical solution adopted by the present invention is:

[0009] The first aspect of the present invention provides a PA-PE composite material, comprising the following components in parts by weight:

[0010]

[0011]

[0012] Preferably, the PA-PE composite material comprises the following components in parts by weight:

[0013]

[0014] According to an embodiment of the present invention, the polyamide includes one or more of polycaprolactam (PA6), polyethylene adipate (PA66), polyω-aminoundecanoyl (PA11), polylaurolactam (PA12), polybutylene adipamide (PA46), polyhexamethylene sebacamide (PA610), polyhexamethylene dodecane diamide (PA612), polydecamethylene sebacamide (PA1010), and semi-aromatic nylon (PA6T). Preferably, the polyamide is selected from at least one of polycaprolactam (PA6) and polyethylene adipate (PA66); more preferably, the polyamide is PA66.

[0015] According to a specific embodiment of the present invention, the PA66 is a modified PA66; in some embodiments, the modified PA66 is filled with at least one of molybdenum disulfide or carbon fiber. In some embodiments, the PA66 can be selected from the H7205 MS (PA66 with 5% molybdenum disulfide added) or H7210CF MS (PA66 with 10% carbon fiber and molybdenum disulfide added). By adding the above PA66, the rigidity, hardness and dimensional stability of the PA-PE material of the present invention are improved, and the grain forming effect of molybdenum disulfide improves the crystal structure, so that the material's load-bearing capacity and wear resistance are improved.

[0016] According to an embodiment of the present invention, the polyethylene includes low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), and high-density polyethylene (HDPE). Preferably, the polyethylene is high-density polyethylene; more preferably, the density of the polyethylene is 0.941-0.965 g / cm 3 .

[0017] High-density polyethylene (HDPE) is a non-polar material with good water resistance. After being compounded with PA, HDPE is dispersed in the PA matrix, which prevents water molecules from diffusing inside the PA matrix, thereby reducing the water absorption of the PA-PE material of the present invention. In some embodiments, the HDPE can be selected from 5421B of CNOOC Shell Petrochemical Co., Ltd., DGDA6098 of Sinopec Qilu Petrochemical Co., Ltd., or GC7260 of PetroChina Liaoyang Petrochemical Co., Ltd.

[0018] According to an embodiment of the present invention, the glass fiber is a hydrolysis-resistant glass fiber; preferably, the glass fiber is a hydrolysis-resistant short glass fiber. According to an embodiment of the present invention, the length of the glass fiber is 3-6 mm; preferably, the length of the glass fiber is 3-4.5 mm. By adding glass fiber, the heat resistance, strength, stiffness, creep resistance, dimensional stability and wear resistance of the PA-PE material of the present invention are improved, the application temperature range is expanded, and the stability is improved. In some embodiments, the glass fiber can be selected from ECS301CL-3-H or ECS301HP-3-H of Chongqing International Composite Materials Co., Ltd.

[0019] According to an embodiment of the present invention, the compatibilizer includes one or more of polyethylene grafted maleic anhydride (PE-g-MAH), ethylene-octene copolymer grafted maleic anhydride (POE-g-MAH), maleic anhydride grafted polybutadiene, polyolefin grafted maleic anhydride (PO-g-MAH), ethylene-vinyl acetate copolymer grafted maleic anhydride (EVAC-g-MAH), polyethylene-glycidyl methacrylate (EGMA), ethylene acrylic acid copolymer, maleic anhydride grafted ethylene propylene rubber (EPDM-g-MAH). Preferably, the compatibilizer is selected from at least one of polyethylene grafted maleic anhydride (PE-g-MAH) and maleic anhydride grafted ethylene propylene rubber (EPDM-g-MAH). More preferably, the compatibilizer is a mixture of PE-g-MAH and EPDM-g-MAH. In some embodiments, the polyethylene grafted maleic anhydride (PE-g-MAH) is high-density polyethylene grafted maleic anhydride (HDPE-g-MAH). In some specific embodiments, the compatibilizer is a mixture of HDPE-g-MAH and EPDM-g-MAH, wherein the mass ratio of HDPE-g-MAH to EPDM-g-MAH is 1-3: 1-3. More preferably, the mass ratio of HDPE-g-MAH to EPDM-g-MAH in the compatibilizer is about 1:1.

[0020] According to a specific embodiment of the present invention, HDPE-g-MAH and EPDM-g-MAH can synergistically improve the compatibility of HDPE and PA. By adding the above-mentioned compatibilizer combination, the compatibility of each component in the PA-PE material of the present invention is improved, the impact strength of the material is increased, the water absorption rate is reduced, the dimensional stability is increased, and the molding performance is improved. In some embodiments, the HDPE-g-MAH can be selected from TY1053H of Dow Chemical Company, USA; the EPDM-g-MAH can be selected from FUSABOND N416 of DuPont Company, USA.

[0021] According to an embodiment of the present invention, the antibacterial agent is a nano antibacterial agent; preferably, the antibacterial agent includes one or more of nano zinc oxide, nano copper oxide and nano lithium carbonate. Adding the antibacterial agent enables the PA-PE material of the present invention to meet the requirements of the food field for good antibacterial properties.

[0022] According to an embodiment of the present invention, the antioxidant includes one or more of a hindered phenol antioxidant, a phosphite antioxidant, a thiobisphenol antioxidant, and a thioether antioxidant. Preferably, the antioxidant includes one or more of the following: 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, pentaerythritol diphosphite distearyl, tris(2,4-di-tert-butylphenyl)phosphite, triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acrylonitrile, 4,4'-thiobis(6-tert-butyl-3-methylphenol), bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and dilauryl thiodipropionate. More preferably, the antioxidant is selected from at least one of 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and pentaerythritol dioctadecyl diphosphite.

[0023] In some embodiments, the antioxidant is a mixture of 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and dioctadecyl pentaerythritol diphosphite. In some specific embodiments, the mass ratio of 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene to dioctadecyl pentaerythritol diphosphite in the antioxidant is 1-3:1-3; more preferably, the mass ratio of 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene to dioctadecyl pentaerythritol diphosphite in the antioxidant is about 1:1.

[0024] According to a specific embodiment of the present invention, the 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene can be selected from the antioxidant MIANOX1330 of Nanjing Milan Chemical Co., Ltd.; the pentaerythritol dioctadecyl diphosphite can be selected from the antioxidant MIANOX618 of Nanjing Milan Chemical Co., Ltd. Antioxidant MIANOX1330 is a high molecular weight polyhedral hindered phenol antioxidant, which has the characteristics of non-coloring, low volatility, good heat resistance, etc. It can effectively prevent thermal oxidation degradation and is particularly suitable for the field of injection molding products processed at high temperatures. Antioxidant MIANOX618 is a phosphite high-temperature antioxidant. Due to the presence of a diphosphite structure and a high content of alkyl trivalent phosphorus, the antioxidant effect is more prominent and is suitable for materials related to the food field. Antioxidant MIANOX1330 and antioxidant MIANOX618 have a good synergistic effect.

[0025] According to an embodiment of the present invention, the auxiliary agent includes one or more of a heat stabilizer, a lubricant, and an anti-ultraviolet agent; preferably, the auxiliary agent includes 0-1 part of a heat stabilizer, 0-1 part of a lubricant, and 0-1 part of an anti-ultraviolet agent; more preferably, the auxiliary agent includes 0.1-0.5 part of a heat stabilizer, 0.1-0.5 part of a lubricant, and 0.1-0.5 part of an anti-ultraviolet agent.

[0026] Preferably, the heat stabilizer includes one or more of an organic salt heat stabilizer, an inorganic salt heat stabilizer, an organic amine heat stabilizer and an organic phenol heat stabilizer; more preferably, the heat stabilizer is an organic salt heat stabilizer. Inorganic salt heat stabilizers have poor compatibility with PA and are easily extracted by water; organic amine and organic phenol heat stabilizers have good compatibility with PA, but are relatively expensive; and organic salt heat stabilizers can ensure that PA does not undergo significant degradation during the molding process, maintain high material performance, and have a better cost-effectiveness ratio. In some embodiments, the heat stabilizer is an organic copper salt heat stabilizer. In some specific embodiments, the organic copper salt heat stabilizer is selected from ThemstabSH3360 of Dongguan Sanhe Chemical Co., Ltd. The addition of Themstab SH3360 can significantly improve the hydrolysis resistance of the PA-PE composite material of the present invention under acidic or alkaline conditions, so that it can effectively resist the corrosion of hot diols, oils, and fats, provide long-term protection for light-colored products, and resist yellowing. In other specific embodiments, the organic copper salt heat stabilizer is selected from Finnre-336 of NOFA Company in the United States. Adding Finnre-336 can avoid the yellowing, brittleness and degradation of mechanical properties of the PA-PE composite material of the present invention caused by thermal oxidative degradation during processing, improve the processing performance during extrusion and injection molding, and allow the product to work at higher temperatures and withstand multiple processing.

[0027] Preferably, the lubricant includes one or more of stearic acid, stearic acid amide, oleic acid amide, calcium stearate, zinc stearate and polyethylene wax.

[0028] Preferably, the anti-ultraviolet agent includes one or more of hindered amines, chlorobenzotriazoles, benzophenones, and hydroxyphenylbenzotriazoles. More preferably, the anti-ultraviolet agent is a chlorobenzotriazole anti-ultraviolet agent. In some embodiments, the anti-ultraviolet agent is 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole. In some specific embodiments, the anti-ultraviolet agent 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole can be selected from the ultraviolet absorber UV-326 of Dongguan Guangsiyuan Polyurethane Materials Co., Ltd. UV-326 is a high-efficiency ultraviolet absorber, resistant to high temperatures, good thermal stability, oil resistance, suitable for polyolefin food-grade products; suitable for use with phenolic antioxidants and phosphite antioxidants.

[0029] The second aspect of the present invention provides a method for preparing a PA-PE composite material, comprising the following steps:

[0030] (1) mixing polyamide, polyethylene, a compatibilizer, an antibacterial agent, an antioxidant, and an additive to obtain a mixed component;

[0031] (2) adding the obtained mixed components into a parallel twin-screw extruder, and then adding the glass fiber into the parallel twin-screw extruder, and sequentially performing extrusion, cooling, and granulation to obtain a PA-PE composite material.

[0032] Preferably, the extrusion temperatures of each zone of the parallel twin-screw extruder in step (2) are: zone 1: 200-230°C, zone 2: 200-230°C, zone 3: 210-245°C, zone 4: 235-250°C, zone 5: 235-250°C, zone 6: 240-255°C, zone 7: 230-245°C, zone 8: 220-230°C.

[0033] Preferably, in the step (2), the obtained mixed components are added to the main feeding port of the parallel twin-screw extruder, and the glass fiber is then added to the side feeding port of the parallel twin-screw extruder.

[0034] Preferably, the vacuum degree of the parallel twin-screw extruder is -0.06-0.1 MPa.

[0035] Preferably, the screw speed of the parallel twin-screw extruder is 200-450 rpm.

[0036] The third aspect of the present invention provides the use of the PA-PE composite material of the first aspect of the present invention or the PA-PE composite material prepared by the method of the second aspect of the present invention as a food contact material.

[0037] According to an embodiment of the present invention, the food contact material includes but is not limited to food packaging materials, food utensils raw materials, and food production equipment raw materials. In some embodiments, the PA-PE composite material of the present invention can be used to prepare food packaging materials, food utensils, and food production equipment. In some embodiments, the PA-PE composite material of the present invention can be used to prepare molded products such as food packaging materials, food containers, food utensils, and food industry equipment. In some specific embodiments, the PA-PE composite material of the present invention is used to prepare tableware and kitchenware.

[0038] The beneficial technical effects of the present invention are:

[0039] (1) The present invention improves the compatibility of PA and PE by adding a compatibilizer, so that the prepared PA-PE composite material has high stability, excellent mechanical properties, low water absorption, and excellent heat resistance, low temperature resistance, acid and alkali resistance, and oil resistance;

[0040] (2) The present invention adds hydrolysis-resistant glass short fibers to maximize the reinforcing effect on the matrix, so that the composite material of the present invention has both good tensile properties and high rigidity, and at the same time enhances wear resistance. The raw material is modified PA66, so that the rigidity, hardness and dimensional stability of the composite material are all improved.

[0041] (3) The present invention further improves the stability of the composite material by adding antioxidants and heat stabilizers; and further improves the antibacterial and antifungal capabilities of the composite material by adding antibacterial agents; the material is very suitable for use in the food field, especially for the preparation of tableware and kitchen utensils. The product prepared from the composite material of the present invention has low migration during contact with food, no odor during cooking, no deformation when heated, stable size, low shrinkage, and good hand strength. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. The examples described below by reference are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0043] Example 1

[0044] A PA-PE composite material, consisting of the following components:

[0045]

[0046] Wherein, the polyamide is modified PA66 (Xinfuda Composite Materials Co., Ltd. MS); the polyethylene is HDPE (5421B of CNOOC Shell Petrochemical Co., Ltd.); the glass fiber is ECS301CL-3-H of Chongqing International Composite Materials Co., Ltd.; the compatibilizer is a mixture of HDPE-g-MAH (TY1053H of Dow Chemical Company, USA) and EGMA-g-MAH (FUSABOND N416 of DuPont Company, USA), and the mass ratio is 1:1; the antibacterial agent is nano zinc oxide; the antioxidant is a mixture of 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl) benzene (antioxidant MIANOX1330 of Nanjing Milan Chemical Co., Ltd.) and dioctadecyl pentaerythritol diphosphite (antioxidant MIANOX618 of Nanjing Milan Chemical Co., Ltd.), and the mass ratio is 1:1; the heat stabilizer is an organic copper salt heat stabilizer (Themstab of Dongguan Sanhe Chemical Co., Ltd. SH3360); the lubricant is calcium stearate; the anti-ultraviolet agent is 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole (Dongguan Guangsiyuan Polyurethane Material Co., Ltd. UV-326).

[0047] The preparation method of the PA-PE composite material of Example 1 comprises the following steps:

[0048] (1) drying the polyamide, polyethylene, compatibilizer, antibacterial agent, antioxidant, thermal stabilizer, lubricant, and anti-ultraviolet agent at 80° C. for 8 hours to make the moisture content less than 0.5%, thereby obtaining dried components;

[0049] (2) Weighing the dried components according to their weight, adding them into a high-speed mixer and mixing for 6 minutes at a speed of 1000 rpm to obtain a mixed component;

[0050] (3) adding the obtained mixed components to the main feed port of a parallel twin-screw extruder, and then adding the glass fiber to the side feed port of the parallel twin-screw extruder, and sequentially performing extrusion, cooling, and granulation to obtain a PA-PE composite material;

[0051] In the step (3), the extrusion temperatures of the parallel twin-screw extruder in each zone are: zone 1: 210°C, zone 2: 210°C, zone 3: 225°C, zone 4: 240°C, zone 5: 240°C, zone 6: 250°C, zone 7: 235°C, zone 8: 225°C; the vacuum degree is -0.06-0.1Mpa, and the screw speed is 350rpm.

[0052] Example 2

[0053] A PA-PE composite material, consisting of the following components:

[0054]

[0055] Wherein, the polyamide is modified PA66 (Xinfuda Composite Materials Co., Ltd. MS); the polyethylene is HDPE (5421B of CNOOC Shell Petrochemical Co., Ltd.); the glass fiber is ECS301CL-3-H of Chongqing International Composite Materials Co., Ltd.; the compatibilizer is a mixture of HDPE-g-MAH (TY1053H of Dow Chemical Company, USA) and EGMA-g-MAH (FUSABOND N416 of DuPont Company, USA), and the mass ratio is 3:1; the antibacterial agent is nano copper oxide; the antioxidant is a mixture of 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl) benzene (antioxidant MIANOX1330 of Nanjing Milan Chemical Co., Ltd.) and dioctadecyl pentaerythritol diphosphite (antioxidant MIANOX618 of Nanjing Milan Chemical Co., Ltd.), and the mass ratio is 1:1; the heat stabilizer is an organic copper salt heat stabilizer (Themstab of Dongguan Sanhe Chemical Co., Ltd. SH3360); the lubricant is zinc stearate; the anti-ultraviolet agent is 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole (Dongguan Guangsiyuan Polyurethane Material Co., Ltd. UV-326).

[0056] The preparation method of the PA-PE composite material of Example 2 comprises the following steps:

[0057] (1) drying polyamide, polyethylene, compatibilizer, antibacterial agent, antioxidant, heat stabilizer, lubricant, and anti-ultraviolet agent at 90° C. for 7 hours to make their water content less than 0.5%, to obtain dried components;

[0058] (2) Weighing the dried components according to their weight, adding them into a high-speed mixer and mixing for 6 minutes at a speed of 1200 rpm to obtain a mixed component;

[0059] (3) adding the obtained mixed components to the main feed port of a parallel twin-screw extruder, and then adding the glass fiber to the side feed port of the parallel twin-screw extruder, and sequentially performing extrusion, cooling, and granulation to obtain a PA-PE composite material;

[0060] Wherein, the extrusion temperatures of each zone of the parallel twin-screw extruder in step (3) are: zone 1: 220°C, zone 2: 220°C, zone 3: 230°C, zone 4: 245°C, zone 5: 245°C, zone 6: 250°C, zone 7: 235°C, zone 8: 225°C; the vacuum degree is -0.06-0.1Mpa, and the screw speed is 400rpm.

[0061] Example 3

[0062] A PA-PE composite material, consisting of the following components:

[0063]

[0064] Wherein, the polyamide is modified PA66 (Xinfuda Composite Materials Co., Ltd. ); the polyethylene is HDPE (Sinopec Qilu Petrochemical Company DGDA6098); the glass fiber is ECS301HP-3-H of Chongqing International Composite Materials Co., Ltd.; the compatibilizer is HDPE-g-MAH (Dow Chemical Company TY1053H); the antibacterial agent is nano lithium carbonate; the antioxidant is 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl) benzene (Antioxidant MI of Nanjing Milan Chemical Co., Ltd. The invention discloses a mixture of a polyol (polyol)-1,4-diol-2-nitropropene (POLY(R)-ANOX1330) and ...618) in a mass ratio of 1:1; the heat stabilizer is an organic copper salt heat stabilizer (Finnre-336 from NOFA, USA); the lubricant is oleic acid amide; the anti-ultraviolet agent is 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole (UV-326 from Dongguan Guangsiyuan Polyurethane Material Co., Ltd.).

[0065] The preparation method of the PA-PE composite material of Example 3 comprises the following steps:

[0066] (1) drying polyamide, polyethylene, compatibilizer, antibacterial agent, antioxidant, heat stabilizer, lubricant, and anti-ultraviolet agent at 75° C. for 9 hours to make the moisture content less than 0.5%, thereby obtaining dried components;

[0067] (2) Weighing the dried components according to their weight, adding them into a high-speed mixer and mixing for 8 minutes at a speed of 800 rpm to obtain a mixed component;

[0068] (3) adding the obtained mixed components to the main feed port of a parallel twin-screw extruder, and then adding the glass fiber to the side feed port of the parallel twin-screw extruder, and sequentially performing extrusion, cooling, and granulation to obtain a PA-PE composite material;

[0069] Wherein, the extrusion temperatures of each zone of the parallel twin-screw extruder in step (3) are: zone 1: 225°C, zone 2: 225°C, zone 3: 235°C, zone 4: 250°C, zone 5: 250°C, zone 6: 255°C, zone 7: 245°C, zone 8: 230°C; the vacuum degree is -0.06-0.1Mpa, and the screw speed is 450rpm.

[0070] Example 4

[0071] A PA-PE composite material, consisting of the following components:

[0072]

[0073] Wherein, the polyamide is modified PA66 (Xinfuda Composite Materials Co., Ltd. H7210CF MS); the polyethylene is HDPE (5421B from CNOOC Shell Petrochemical Co., Ltd.); the glass fiber is ECS301CL-3-H from Chongqing International Composite Materials Co., Ltd.; the compatibilizer is HDPE-g-MAH (TY1053H from Dow Chemical Company, USA) and EGMA-g-MAH (FUSABOND from DuPont, USA) N416), with a mass ratio of 1:1; the antibacterial agent is nano zinc oxide; the antioxidant is a mixture of 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (Nanjing Milan Chemical Co., Ltd. antioxidant MIANOX1330) and pentaerythritol dioctadecyl diphosphite (Nanjing Milan Chemical Co., Ltd. antioxidant MIANOX618), with a mass ratio of 1:1; the lubricant is calcium stearate; the anti-ultraviolet agent is 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole (Dongguan Guangsiyuan Polyurethane Material Co., Ltd. UV-326).

[0074] The preparation method of the PA-PE composite material of Example 1 comprises the following steps:

[0075] (1) drying the polyamide, polyethylene, compatibilizer, antibacterial agent, antioxidant, lubricant, and anti-ultraviolet agent at 80° C. for 8 hours to make the moisture content less than 0.5%, thereby obtaining dried components;

[0076] (2) Weighing the dried components according to their weight, adding them into a high-speed mixer and mixing for 6 minutes at a speed of 1000 rpm to obtain a mixed component;

[0077] (3) adding the obtained mixed components to the main feed port of a parallel twin-screw extruder, and then adding the glass fiber to the side feed port of the parallel twin-screw extruder, and sequentially performing extrusion, cooling, and granulation to obtain a PA-PE composite material;

[0078] In the step (3), the extrusion temperatures of the parallel twin-screw extruder in each zone are: zone 1: 210°C, zone 2: 210°C, zone 3: 225°C, zone 4: 240°C, zone 5: 240°C, zone 6: 250°C, zone 7: 235°C, zone 8: 225°C; the vacuum degree is -0.06-0.1Mpa, and the screw speed is 350rpm.

[0079] Comparative Example 1

[0080] A modified PA66 material: Xinfuda Composite Materials Co., Ltd. H7210CF MS.

[0081] Comparative Example 2

[0082] The preparation method of the PA-PE composite material of Comparative Example 2 refers to that of Example 1, except that the amount of glass fiber used is 5 kg; the remaining raw material components, amounts used and preparation methods are the same as those of Example 1.

[0083] Comparative Example 3

[0084] The preparation method of the PA-PE composite material of Comparative Example 3 refers to that of Example 1, except that the amount of polyethylene used is 8 kg; the remaining raw material components, amounts used and preparation methods are the same as those of Example 1.

[0085] Comparative Example 4

[0086] The preparation method of the PA-PE composite material of Comparative Example 4 refers to that of Example 1, except that no antioxidant is added; the remaining raw material components, dosages and preparation methods are the same as those of Example 1.

[0087] The weights of the raw material components of Examples 1-4 and Comparative Examples 1-4 are shown in Table 1.

[0088] Table 1. Raw material components of Examples 1-4 and Comparative Examples 1-4

[0089]

[0090] Test Case

[0091] The material samples of Examples 1-4 and Comparative Examples 1-4 were subjected to performance tests; wherein the tensile strength and elongation at break were tested in accordance with GB / T 1040-2018, the notched impact strength was tested in accordance with GB / T 1043-2018, and the water absorption (5 days) was tested in accordance with GB / T 1034-2008; Evaporation residue test (used to evaluate the migration of the material): the above material samples were taken and the samples were placed at 1 cm 2 The contact area is soaked with 2 mL of food simulant, and 4% (v / v) acetic acid solution is used as the food simulant. The simulated soaking is carried out at a contact time of 30 minutes or 2 hours and a temperature of 95°C. The soaked food simulant is evaporated and dried to obtain the evaporation residue of the sample in 4% acetic acid solution. The analysis method of 4% (v / v) acetic acid evaporation residue is carried out in accordance with Part 5 of GB / T5009.60-2003. The performance test results are shown in Table 2.

[0092] Table 2. Performance test results of materials of Examples 1-4 and Comparative Examples 1-4

[0093]

[0094] As can be seen from the above table, the PA-PE material of the present invention has both excellent mechanical properties and high stability, low water absorption, and less migration at high temperature (less evaporation residue), and is suitable for making food contact materials or utensils. Compared with Comparative Example 1, the composite material of the present invention has significantly better mechanical properties and stability; compared with Comparative Example 2, the composite material of the present invention has higher tensile strength and high temperature stability; compared with Comparative Example 3, the composite material of the present invention has higher elongation at break and notched impact strength, and better high temperature stability; compared with Comparative Example 4, the high temperature stability of the composite material of the present invention is significantly better. The present invention improves the toughness, elongation at break and water resistance of the material by compounding an appropriate amount of HDPE on the basis of PA; adds a suitable compatibilizer to improve the bonding force between PA and HDPE, the interface is tightly bonded, and the compatibility is increased; adds an appropriate amount of glass fiber to increase the rigidity and stability of the composite material; adds antioxidants and the like to further enhance the stability of the composite material in high temperature and acidic environments to reduce the migration amount.

[0095] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. Application of a PA-PE composite material as a food contact material, characterized in that: The PA-PE composite material comprises the following components in parts by weight: The polyamide is modified PA66, and the modified PA66 is filled with at least one of molybdenum disulfide or carbon fiber; The polyethylene is high-density polyethylene; the density of the polyethylene is 0.941-0.965 g / cm 3 ; The glass fiber is a hydrolysis-resistant short glass fiber; the length of the glass fiber is 3-6 mm; The compatibilizer is a mixture of polyethylene grafted with maleic anhydride and maleic anhydride grafted with EPDM rubber; The antibacterial agent includes one or more of nano zinc oxide, nano copper oxide and nano lithium carbonate; The antioxidant is a mixture of 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and pentaerythritol dioctadecyl diphosphite; The auxiliary agent includes 0.1-0.5 parts of heat stabilizer, 0.1-0.5 parts of lubricant, and 0.1-0.5 parts of anti-ultraviolet agent; The anti-ultraviolet agent is a chlorobenzotriazole anti-ultraviolet agent.

2. The use of the PA-PE composite material according to claim 1 as a food contact material, characterized in that: The PA-PE composite material is prepared by a method comprising the following steps: Mixing polyamide, polyethylene, a compatibilizer, an antimicrobial agent, an antioxidant, and an additive to obtain a mixed component; The obtained mixed components are added into a parallel twin-screw extruder, and then the glass fiber is added into the parallel twin-screw extruder, and extrusion, cooling and granulation are performed in sequence to obtain a PA-PE composite material.

Citation Information

Patent Citations

  • Polyamide composite material and preparation method thereof

    CN104725839A

  • Antibacterial nylon composite and preparation method thereof

    CN106280423A

  • Preparation method of PA66 alloy material

    CN113292850A